Physical activity and metabolic risk in university students Lima-Peru 2016 - Pereyra-Zaldívar, Héctor (2021)
Numerous studies show a high prevalence of cardiovascular and metabolic diseases in adults and older adults, although their frequency increases in young people. An exploratory, descriptive study was carried out on first-year medical students from the Universidad Nacional Mayor de San Marcos (UNMSM), to know the physical activity levels and the criteria for metabolic syndrome (MS). The study was accepted by an Ethics Committee of the Faculty of Medicine. Statistical analysis was performed with Stata v6. 56.7% of the students are 17-19 years old, and 53.3% are female; 56.7% have a monthly per capita family income greater than 500 soles, and 76.7% come from urban Lima. 83.4% had limited physical activity, being the most frequent MS  components: elevated abdominal circumference (36.7%) and low levels of high-density cholesterol (23.3%). The only variable with statistical association with MS (p = 0.0389) was Abdominal Circumference-AC. The Body Mass Index-BMI is the only variable associated with AC (p = 0.007). Despite the limited sample size, the results indicate limited physical activity and significant cardiometabolic risk, exceptionally high abdominal circumference, which is why studies in other university populations are necessary to influence university wellness policies for preventive purposes.